2020
DOI: 10.25122/jml-2019-0149
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Cooperative Flipped Learning with Individual Flipped Learning in a Biochemistry Course

Abstract: The aim of this study was to compare a cooperative flipped learning method with an individual flipped learning method in a biochemistry course. In a quasi-experiment, convenience sampling was employed to select 61 biochemistry students, who were then randomly divided into three groups. The experimental groups were trained separately using the cooperative flipped learning and individual flipped learning methods in seven sessions. The control group was trained using the conventional method. The groups were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Third, flipped classroom learning gave students more time to learn from easily accessible modules [53], [54]. With this extra time, students can learn everything they need about the geometry course from an Android module.…”
Section: Discussionmentioning
confidence: 99%
“…Third, flipped classroom learning gave students more time to learn from easily accessible modules [53], [54]. With this extra time, students can learn everything they need about the geometry course from an Android module.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating technology in flipped language classes can help students overcome time and space limitations for language use (Asiri et al ., 2021). FL has significant potential in language learning settings (Andujar et al ., 2020; Arslan, 2020; Jafarkhani and Jamebozorg, 2020) and addresses the Saudi MOE's goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The case study results reported by Ng and Nicholas [25] show that students who follow a progressive instructional learning model can consistently complete all the required tasks of an online learning program. Although the effects of cooperative learning on classroom interactions have been studied [23,26,27], few studies have focused on students' perspectives, specifically after they sequentially engage in several different learning methods [25]. Therefore, this study divides the one-semester course into three parts and adopts three different learning methods, from TL to IFL and then CFL, to increase the diversity of learning styles.…”
Section: Progressive Interactive Learning Experiencementioning
confidence: 99%